2007
DOI: 10.1007/s00436-007-0651-3
|View full text |Cite
|
Sign up to set email alerts
|

Sequence diversity and differential expression of Tc52 immuno-regulatory protein in Trypanosoma cruzi: potential implications in the biological variability of strains

Abstract: Trypanosoma cruzi is highly heterogeneous in terms of genetics and biological properties. To explore the diversity of T. cruzi, we focused our study on the T. cruzi Tc52 protein playing a critical immunosuppressive role during infection. Sequence variability and expression levels of this virulence factor were analysed in various strains. Among the 40 amino acid substitutions detected in the Tc52 coding sequences, three substitutions may have an impact on protein activity or function, as two are localized in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Natural populations of T. cruzi are very heterogeneous in biological, biochemical, immunological, and molecular features (Miles 2003;Dost et al 2004;Mathieu-Daudé et al 2007;Santos-Mallet et al 2008;Venegas et al 2010); consequently, different strains from endemic areas might be responsible for distinct clinical manifestations and chemotherapy response (Andrade 1999). In this context, previous works reported that T. cruzi strains produced different amounts of proteases, including the major cysteine protease named cruzipain (Fampa et al 2008(Fampa et al , 2010Gomes et al 2009;Kikuchi et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Natural populations of T. cruzi are very heterogeneous in biological, biochemical, immunological, and molecular features (Miles 2003;Dost et al 2004;Mathieu-Daudé et al 2007;Santos-Mallet et al 2008;Venegas et al 2010); consequently, different strains from endemic areas might be responsible for distinct clinical manifestations and chemotherapy response (Andrade 1999). In this context, previous works reported that T. cruzi strains produced different amounts of proteases, including the major cysteine protease named cruzipain (Fampa et al 2008(Fampa et al , 2010Gomes et al 2009;Kikuchi et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Despite its broad genetic diversity, three major lineages, named T. cruzi I, II and III, have been identified in the parasite population [81]. Studies with a number of molecular markers revealed that parasites belonging to the T. cruzi I lineage have lower genetic variability compared to T. cruzi II, and III [8284]. The great genetic diversity observed in T. cruzi (and more precisely, in T. cruzi II strains) may play an important role in pathogenesis and survival of the parasite within its different hosts.…”
Section: Mismatch Repairmentioning
confidence: 99%
“…Metacyclic trypomastigotes, obtained from the differentiation of late stationary phase epimastigotes, were used to initiate infection of mouse fibroblasts (L929). Trypomastigotes and amastigotes were produced and harvested as previously described [12]. Pellets for RNA purification were processed immediately in lysis buffer.…”
Section: Methodsmentioning
confidence: 99%